Tagetes dombeyi (Asteraceae, Tageteae), a new species from the Central Andes first collected in the 18th century - Darío Javier Schiavinato; Diego Germán Gutiérrez; Adriana Bartoli (Rodriguésia, 2023)
Abstract Tagetes dombeyi (Asteraceae, Tageteae), a new species from the Central Andes first collected in the 18th century. A new annual species of Tagetes from the Central Andes of Peru and Bolivia, T. dombeyi, is described and illustrated based on herbarium collections and photographs of the plants in their habitat. Tagetes dombeyi is closely related to Tagetes imbricata, Tagetes multiflora - both of which can occasionally be found mixed with the former on the same herbarium sheet - and Tagetes iltisiana. However, they can be distinguished by diagnostic characters of leaf, corolla, and pappus. A morphological description is provided along with an illustration, a range map, and a key to differentiating the Tagetes species that inhabit Peru and Bolivia.